A focus on collaboration: Fostering Australian screen production students’ teamwork skills - Dooley, Kath; Sexton-Finck, L. (Curtin University, 2017)
Recent research undertaken in Australia and abroad suggests that the development of effective collaboration skills is a significant factor affecting the successful employment of graduate screen practitioners. This article outlines the results of a study that examined student response to the explicit teaching of collaboration skills in an Australian screen production course. The authors report on an empirical research project undertaken in 2015 and 2016 in the Department of Screen Arts at Curtin University, Western Australia. This involved two cohorts of second year screen production students (83 in total), and aimed to foster students’ teamwork skills. The activities and resources shared with students encouraged an interrogation of contemporary models of filmmaking collaboration, the use of group contracts to identify shared values of teamwork and the implementation of activities designed to improve students’ awareness of various collaboration styles. Outcomes were measured by both qualitative and quantitative means through student surveys administered at both the beginning and end of the unit of study. The results of these surveys suggest a change in student attitudes towards collaboration, particularly in regards to the value of communication. The authors aim to disseminate these findings and to encourage further discussion and study in this area. The article builds a case for more attention being placed on the explicit teaching of teamwork and collaboration skills in University screen production courses.